Women, ritual, and power : placing female imagery of God in Christian worship - Ursic, Elizabeth (State University of New York Press, 2014)
Many Christians do not know the Bible contains female images of God because they have never heard nor seen them in church. In Women, Ritual, and Power, Elizabeth Ursic gives the reader insight into four Christian communities that worship God with female imagery, both as a worship focus and a community identity. These Methodist, Presbyterian, Lutheran, and Catholic congregations operate within their established church denominations and are led by either ordained Protestant ministers or vowed Catholic sisters. Because expressing God-as-She can expose strident claims for maintaining God-as-He, this book shows not only how patriarchy continues to operate in churches today, but also how it is being successfully challenged through liturgy.